Utilization of the Ibis Paint X Application in Fashion Design Learning for Class XI of Imelda Tourism Vocational School, Medan: Utilization of the Ibis Paint X Application in Fashion Design Learning for Class XI of Imelda Tourism Vocational School, Medan - br Tarigan, Oky Tamara; Sari, Putri Winda; Ampera, Dina (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The Ibis Paint X design application is a medium for fostering creativity. This study aims to utilize digital design applications as a learning tool and determine students' abilities in designing clothes. The type of research used is classroom action research (CAR). The object of this research is Fashion Design, and the subjects of this research are students of class XI Fashion Design at SMK Pariwisata Imelda Medan (totaling 29 students). Based on the Observation Data Results, it can be seen that there are still many students in the Fashion Design subject whose scores have yet to reach competency or are below the KKM. The research method used by the author is the Classroom Action Research (CAR) method. Classroom Action Research (CAR) is research teachers conduct in their classes through self-reflection to improve their performance and increase learning. The comparison diagram of cycle I, cycle II, cycle III, and final grades for the academic year 2022/2023-2023/2024 shows a comparison of the final grades of students who completed the academic year 2022/2023-2023/2024, namely 36% - 41%, and those who did not complete 59% -64%. In cycle I, 39% was completed, and 50% still needed to complete. Meanwhile, in cycle 2, the grades of students who completed were 79%, and those who did not complete 21%. From the results of this study, it can be seen from the comparison of student grades in the Fashion Design subject that it has increased. Learning Fashion Design by utilizing the Ibis Paint X application learning media can improve the Fashion Design learning process, as seen from the increase in the percentage of student grades from cycle I and increasing in cycle II.